2018
DOI: 10.4317/medoral.22449
|View full text |Cite
|
Sign up to set email alerts
|

Buccal fat pad removal to improve facial aesthetics: an established technique?

Abstract: BackgroundBuccal fat pad (BFP) is a singular structure between the facial muscles. Its removal may enhance the zygomatic prominences resulting in an inverted triangle of beauty. Objective: The aim of this study was to perform a systematic review of literature about BFP removal for facial aesthetic improvement. In order to answer the following research question: What are the indications, complication types and rates, surgical techniques and outcomes of the technique?Material and MethodsThe initial search in Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
35

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 17 publications
0
39
0
35
Order By: Relevance
“…However, another report by Niada et al [ 44 ] demonstrated no differences in viability, proliferation, clonogenicity and adipogenic, osteogenic, or chondrogenic differentiation between pASCs from subcutaneous interscapular fat and buccal fat pads. Interestingly, this data supported future clinical applications of stem cells from buccal fat, the depot that is discarded tissue during cosmetic surgery for cheek reduction in humans [ 46 ]. Moreover, Burk et al [ 38 ] found that adipose tissue provided a higher number of cells per tissue unit as compared to umbilical cord blood or flexor tendon.…”
Section: Basic Biology Of Ascs Isolated From Livestockmentioning
confidence: 67%
“…However, another report by Niada et al [ 44 ] demonstrated no differences in viability, proliferation, clonogenicity and adipogenic, osteogenic, or chondrogenic differentiation between pASCs from subcutaneous interscapular fat and buccal fat pads. Interestingly, this data supported future clinical applications of stem cells from buccal fat, the depot that is discarded tissue during cosmetic surgery for cheek reduction in humans [ 46 ]. Moreover, Burk et al [ 38 ] found that adipose tissue provided a higher number of cells per tissue unit as compared to umbilical cord blood or flexor tendon.…”
Section: Basic Biology Of Ascs Isolated From Livestockmentioning
confidence: 67%
“…The second case is the procedure for the removal of the buccal fat pad () (also called bichectomy) for aesthetic purposes. A recent published systematic review () found only case reports and case series reporting on the effects of this procedure. In other words, no randomized study was identified in this systematic review, and the case reports and case series were rated as having a high risk of bias ().…”
Section: Figmentioning
confidence: 99%
“…A recent published systematic review () found only case reports and case series reporting on the effects of this procedure. In other words, no randomized study was identified in this systematic review, and the case reports and case series were rated as having a high risk of bias (). Side effects, such as a haemorrhage and facial asymmetry, were reported in four of the eight studies included.…”
Section: Figmentioning
confidence: 99%
“…O sucesso do procedimento pode estar associado ao excelente suprimento sanguíneo da região, fácil mobilização e morbidade mínima (Mannelli et al 2019). A taxa de complicação do procedimento é de 8,45%, sendo mais frequentes os edemas, hematomas, infecções e lesão dos vasos faciais (Klüppel, Marcos, Research, Society and Development, v. 9, n. 10, e4949108921, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8921 4 Shimizu, Silva, & Silva, 2018); Moura, Spin, Spin-Neto, & Pereira-Filho, 2018). Esse trabalho tem como objetivo relatar um caso de complicação mediata de lipectomia bucal e discutir prováveis fatores que determinaram esse evento, bem como as condutas adotadas no manejo desta intercorrência.…”
Section: Introductionunclassified